A half-century of automata theory : celebration and inspiration - Salomaa, Arto; Wood, Derick, 1940-; Yu, Sheng (World Scientific, 2001)
Annotation Eleven pioneers in the field reminisce about the development of automata theory and suggest possible future directions for the field, in these seven papers from a July 2000 symposium held at the University of Western Ontario, Canada. Specific topics include hazard algebras, undecidability and incompleteness results in automata theory, playing infinite games in finite time, gene assembly in ciliates, and compositions over a finite domain. This work lacks a subject index. Salomaa is affiliated with the Turku Center for Computer Science, Finland. Annotation c. Book News, Inc., Portland, OR (booknews.com).